Hunting behaviour in West African forest leopards - Jenny, David; Zuberbühler, Klaus (My University, 2005)
La panthère Panthera pardus est un prédateur majeur de mammifères dans l’écosystème de la forêt pluviale en Afrique Occidentale. La plupart des renseignements sur le comportement de chasse des panthères est tirèe d’études menées dans des habitats ouverts de la savane, tandis que peu est connu sur les panthères forestières. Les données que nous avons rassemblées par radio-émetteurs et les analyses des crottes montrent plusieurs différences entre les panthères forestières et des populations de savane. Les panthères forestières sont des chasseurs diurnes et crépusculaires qui suivent le schéma d'activité de leur proie. Ils déploient des différences saisonnières et développent des préférences de proie fortement individualisées. Nos conclusions défient l'image répandue des panthères comme prédateurs opportunistes nocturnes., The leopard (Panthera pardus) is a major predator of mammals within the rainforest ecosystem of West Africa. Most of the available information on leopard hunting behaviour comes from studies conducted in open savannah habitats, while little is known about forest leopards. Our radio-tracking data and scat analysis show that forest leopards differ in various ways from the savannah populations. Forest leopards are diurnal and crepuscular hunters who follow the activity pattern of their prey species. They exhibit seasonal differences in activity patterns, and they develop highly individualized prey preferences. These findings challenge the widespread notion of leopards as opportunistic nocturnal predators.
Keywords: predation; carnivore; taï forest; selective hunting; monkey alarm calls